中国普通话房屋建筑量词使用上的统计与对比 = Statistical comparison of Mainland Mandarin Chinese classifiers on buildings and housing - 吴美琪 Wu, Meiqi (2016)
量词是表示事物、动作数量的单位词。在现代汉语当中，量词的使用频率很高，其范围也很广。然而，随着时代的改变，许多词汇的意思也跟着在改变，量词也不例外。修饰同一类名词的量词在使用上会因为受到方言的影响或是文体的考量而有些差异。另一方面，人们也会因为名词的某一些特征而选择使用不同的量词，即使这些量词的定义相同或相近。然而，对于这些量词在使用上的区别，还有待探讨。本文将在语料库在线的基础上，计算出普通话中使用范围相近的几个和房屋、建筑等有关的量词，尤其是普通话使用者常混淆的量词，并对这些量词的名词搭配作进一步的统计与分析。从而探讨中国普通话中，该类量词使用上的差异。本文希望透过这次的研究能够补充前人对于量词研究的不足，并试将相似的量词区分开来。本文也希望能够提醒教育者在华语教学时，多注意这些量词的使用。Classifier, or sometimes known as a counter word, is a word or affix that is used to accompany nouns and considered to have the function to classify the noun depending on the type of its referent. In the Chinese language, classifiers play an important role in grammar due to their high usage and there is a wide range of classifiers in the system. However, language changes with time, meanings and functions of words including classifiers changes as well. Different classifiers may accompany a same noun due to influence from dialects or in different literary form. Its usage is also in accordance to the perception of things by different people. Even though the research of classifiers has long been within the scopes of researchers, discussions of the functions of classifiers with similar meanings were within a small scale. This paper will be looking into classifiers of buildings and housing with similar meanings in the Mainland Mandarin Chinese, also known as pu tong hua. Due to the fact that these classifiers share similar meanings in the dictionary, people are often confused with the difference between them. Data of the selected classifiers will be collated from a corpus and sorted out. Next, with the help of Fisher’s exact test, a statistical significance test used in the analysis of contingency tables, the degree of association of the classifiers and accompanied noun will be calculated and compared. The aim of this paper is to discover the differences in the functions of classifiers that appear to be the same, and also to attract further studies towards buildings and housing classifiers in Chinese.